The Effectiveness Of Mock Feedback According To Mixed Learning In Learning The Skill Of Peaceful Scoring In Basketball For First-Stage Students - Abdulhafed, Omar Abdulghfoor (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to find out the effectiveness of false feedback according to the combination of learning with basketball skill that achieves a peaceful goal, as the sample was purposefully selected with a total of 30 students from the College of Physical Education and Sports Sciences/ first stage of Al Mustansiriya University. The researcher used the experimental method (for the two equal groups), and used the electronic educational units that include pictorial feedback for the purpose of presenting the skill in an accurate and interesting way. Here a pilot field study began with the aim of investigating the effect of false feedback using blended learning in learning the skill of nonviolent recording. Here, the research problem focused on not using modern methods in general, especially in the game of basketball in education, and not using formal nutrition in learning skills. Where the researcher directed the use of methods that break the monotony and help in learning the skill faster and more accurately, and contribute to the focus of learning the skill of peaceful scoring and consolidating the skill in the mind of the learner correctly and for a long time. The researcher assumed that there were statistically significant differences between the pre and posttests of the skill of peaceful scoring for basketball between the sample members. When the presentation and discussion of the results were concluded, the researcher concluded that the educational curriculum that was used in the e-learning units for feedback is an achievement for Rh’s aim for the peaceful recording of its positive impact and effective learning. The researcher recommended the necessity of education and learning on how to use electronic educational units, and interest in using modern technology in teaching skills faster and for group sports activities to diversify their skills.